PWE-057 A Composite Measure Of Colonic Intubation (circ) Is Better Able To Distinguish Performance Of Colonoscopy And Is Associated With Higher Polyp Detection Rates. (9th June 2014) - Valori, R; Damery, S; Swarbrick, E; Williams, G; Anderson, J; Donnelly, M; Gavin, D
Abstract : Introduction: Caecal intubation rate (CIR) is a key performance indicator of colonoscopy. CIR with acceptable tolerance is only achieved in some patients with more sedation. As most colonoscopists achieve >90% intubation, CIR alone cannot define excellence. This study proposes a more discerning, composite measure of colonoscopy intubation (CIR C ) combining CIR, patient comfort and sedation. Characteristics of patient, unit, equipment and colonoscopist associated with CIR C, and the relation of CIR C to pathology detection are reported. Methods: Data from 20085 colonoscopies reported in the 2011 UK national audit (Gut 2013;62:242–249) were used for this analysis. The CIR C was defined as percentage of procedures achieving caecal intubation with median dose of midazolam or less, and nurse assessed comfort score of 1–3 (max 5). Multivariate analysis using binary logistic regression assessed patient, unit and colonoscopist factors in order to derive Odds Ratios (ORs) and 95% confidence intervals (CIs) for factors independently associated with CIR c after controlling for effects of all model variables. ORs have a significance level of <0.001 unless stated. Results: Overall achievement of CIR C was 54.1% (n = 10865 procedures). The CIR C was better able to distinguish differences in performance than single measures such as CIR and polyp detection. Older age, male sex (OR 1.40; CI:1.32–1.49), adequate or excellent bowel prep and FOBT screen positive as indication were all associated with a higher chance of achieving CIR C . Unit (JAG) accreditation (OR 1.26; CI 1.16–1.35) and the presence of one or more magnetic imagers in the unit (OR 1.29; 1.19–1.40) were associated with higher CIR C . Surgical speciality, greater annual volume, fewer years' experience and higher training/trainer status were associated with higher CIR C . Achieving the CIR C was associated with significantly higher polyp detection rates (OR 1.12; 1.04–1.20) and higher cancer detection rates (OR 1.14; 0.98–1.32, p = 0.10). Conclusion: The CIR C provides a richer picture of colonoscopic intubation than CIR alone and is better able to discern factors associated with intubation competence in relation to patients, units, equipment and colonoscopists. Unit (JAG) accreditation was associated with higher CIR C . Colonoscopists who perform more procedures, who have more experience of training or being trained, who have practised fewer years and who are in a surgical speciality had significantly higher rates of CIR C . The CIR C was associated with a significantly higher polyp detection rate. It is proposed that CIR C replaces CIR as the key performance indicator for intubation of the colon. Disclosure of Interest: None Declared.